Integration of Mobile Health Apps and Web-Based Interventions in the Self-Management of Low Back Pain: A Systematic Review - Modesto, Gonçalo Miguel Xavier (2018)
Trabalho Final do Mestrado Integrado em Medicina apresentado à Faculdade de Medicina